BUYUK IPAK YOʻLI MEROSI: OʻZBEKISTON VA XITOY MUNOSABATLARI - Sattorova Dilnavoz (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This research provides an extensive academic inquiry into the historical continuum and contemporary transformation of Uzbekistan-China relations, conceptualized through the enduring legacy of the Great Silk Road. Examining the trajectory from ancient transcontinental trade dynamics to the modern structural frameworks of the Belt and Road Initiative (BRI), the study analyzes how historical memory functions as a diplomatic catalyst in contemporary geopolitics. It investigates the mechanisms of strategic partnership, economic integration, and cultural synthesis that define bilateral interactions in the Central Asian macro-region. The research concludes that the modern strategic alignment between Tashkent and Beijing represents a sophisticated re-functionalization of historical trade corridors, positioning Uzbekistan as a critical logistical hub and transitioning regional dynamics from geopolitical fragmentation to collective geoeconomic connectivity.